A SiC high-temperature Pressure Sensor Operating in Severe Condition - Haojie Lv; Huiyong Yu; Guoqing Hu (Institute of Advanced Engineering and Science, 2012)
The tranditional MEMS pressure sensor based on Silicon (Si) material has not been suitable for operating in severe condition such as high-temperature (>500°C). However, as an alternative material, Silicon Carbide (SiC) can be used in hash environment due to its unique properties. Hence this paper presents a touch mode capacitive pressure sensor with double-notches structure, which employs a special SiC-AlN-SiC sandwich structure to achieve high-accuracy pressure measurement in high-temperature environment. In order to get the relation of capacitance and external pressure, the large deflection theory is applied in simulation analysis of the diaphragm deformation. At the same time, the sandwich structure and technical process of the sensor are studied in the paper. The results showed that the sensor has excellent high-temperature performance due to application of SiC and AlN materials, and the sensor has higher sensitivity and longer linear range than traditional single-cavity structure. Consequently, the sensor can be applied to accuracy pressure measuremet in high-temperature and harsh environment. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1692